2020
DOI: 10.1177/2050312120965316
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy after tibial plateau fracture fixation: A systematic review of the literature

Abstract: Background: Tibial plateau fractures are frequent injuries that orthopaedic surgeons face. It has been reported that they have a significant negative impact on the patients’ lives, decreasing their quality of live, keeping them of work for long periods of time and reducing their activity levels. Aim: Interestingly, there is not enough focus in the literature about the post-operative rehabilitation of these patients. The aim of the present review is to investigate this field of the literature and try to give an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 48 publications
(70 reference statements)
0
20
0
Order By: Relevance
“…THFs are a type of common and severe injury, and their later developmental complications such as traumatic arthritis, muscle and bone atrophy, and joint stiffness can cause functional problems in the knee of the patients and increase the socioeconomic burden [ 22 ]. A systematic review demonstrated that tibial plateau fractures have a lower return rates to sport compared with other types of fractures, and only 60% patients can recover to the preinjury level of sport [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…THFs are a type of common and severe injury, and their later developmental complications such as traumatic arthritis, muscle and bone atrophy, and joint stiffness can cause functional problems in the knee of the patients and increase the socioeconomic burden [ 22 ]. A systematic review demonstrated that tibial plateau fractures have a lower return rates to sport compared with other types of fractures, and only 60% patients can recover to the preinjury level of sport [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The significance of early mobilisation and range of knee joint motion exercises has been apparent in literature in the past 40 years [4,12]. A research performed by Gabriel showed that involvement in physiotherapy has a beneficial effect on gaining confidence, enhancing gait in post-operative physiotherapy [13].…”
Section: Discussionmentioning
confidence: 99%
“…Intraarticular tibia fractures are widely referred as tibial plateau fractures. The two main age ranges exist, first cohort includes younger men suffering from heavy impact trauma, whereas second is older women suffering from limited injury [4]. Such fractures are linked to adverse results, because of reasons such as the damage of cartilage but also soft tissue envelopes, complications like compartment syndrome, postoperative infection, knee dysfunction or rigidity, or even post-traumatic osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%
“…Accelerated rehabilitation is thought to expedite the function recovery and prevent joint conglutination [8][9]. Early knee ROM exercises, quadriceps strengthening and proprioception exercises should be encouraged for a good nal outcome [10,16]. We believe that the best approach to rehabilitation after fracture is a training strategy coordinated by a multidisciplinary team for the individual to achieve the highest possible level of function.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the team-based perioperative rehabilitation approach help improved the functional status of patients after knee fracture surgery and shortened the time of postoperative recovery. A recent systematic reviews demonstrated that the fucus on post-operative rehabilitation effect of tibial plateau fracture is scarce and controversial [10]. More research needs to be performed to determine a better postoperative rehabilitation pattern.…”
Section: Discussionmentioning
confidence: 99%